2022
DOI: 10.2174/1389203723666220914120325
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Role of NRF2 Signalling in Cancer

Abstract: Nuclear factor erythroid 2 (NFE 2) - related factor 2 (NFE2L2 or NRF2) is one of the transcription factors predominantly related to the expression of antioxidant genes. NRF2 is found to play a pivotal role in the control of redox potential in several tumor characteristics including cancer cell metabolism, stem-cell-like characteristics, tumor aggressiveness, invasion, and metastasis. Further, it was recently discovered that the noncanonical pathway of NRF2 activation was involved in carcinogenesis. Cancer-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
0
2
0
Order By: Relevance
“…Nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2), known as a transcription factor, is essential for keeping the balance of oxidative stress, regulating metabolism and modulating inflammation 29 . Oxidative stressors or electrophiles dissociates the Nrf2 from Keap‐1, prevents Nrf2 from degrading and increases nuclear accumulation of Nrf2 30 . Previous studies have demonstrated that Nrf2 could directly inhibit the inflammatory cytokines transcription of immune cells and indirectly limit the inflammatory process through modulating HO‐1 expression 31,32 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2), known as a transcription factor, is essential for keeping the balance of oxidative stress, regulating metabolism and modulating inflammation 29 . Oxidative stressors or electrophiles dissociates the Nrf2 from Keap‐1, prevents Nrf2 from degrading and increases nuclear accumulation of Nrf2 30 . Previous studies have demonstrated that Nrf2 could directly inhibit the inflammatory cytokines transcription of immune cells and indirectly limit the inflammatory process through modulating HO‐1 expression 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…29 Oxidative stressors or electrophiles dissociates the Nrf2 from Keap-1, prevents Nrf2 from degrading and increases nuclear accumulation of Nrf2. 30 Previous studies have demonstrated that Nrf2 could directly inhibit the inflammatory cytokines transcription of immune cells and indirectly limit the inflammatory process through modulating HO-1 expression. 31,32 Nrf2 participate in immune cell differentiation, including macrophage, dendritic cell and some subtypes of T cells.…”
Section: Introductionmentioning
confidence: 99%